Knowledge, attitudes and practices analysis, prevalence and molecular detection of Neospora caninum and Toxoplasma gondii in livestock in the Khomas region of Namibia - Matjila, P.T. (Paul Tshepo) (University of Pretoria, 2024)
Thesis (PhD (Veterinary Science))--University of Pretoria, 2023.